2015
DOI: 10.5115/acb.2015.48.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Perception of MBBS students to "flipped class room" approach in neuroanatomy module

Abstract: A flipped classroom is a learner centered approach in which the learner is responsible to attend the class with basic understanding of the subject to fully participate and engage in discussions. The aim of this study was to evaluate students' perception of flipped classroom approach for neuroanatomy module and assess the impact on their performance and attitudes. The subject chosen to evaluate the flipped classroom model for first year medical students was clinical neuroanatomy. One hundred and thirty first ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 11 publications
5
65
0
7
Order By: Relevance
“…Preclinical application of FC elements was concentrated on the basic sciences (Table 2), such as biochemistry11,12 and the anatomical sciences 1315. The incorporation of FC pedagogy in medical anatomy classes has been suggested to be driven, at least in part, by markedly reduced curricular time afforded to the teaching of the subject 15.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical application of FC elements was concentrated on the basic sciences (Table 2), such as biochemistry11,12 and the anatomical sciences 1315. The incorporation of FC pedagogy in medical anatomy classes has been suggested to be driven, at least in part, by markedly reduced curricular time afforded to the teaching of the subject 15.…”
Section: Resultsmentioning
confidence: 99%
“…14,19,25,27 Other resources frequently provided to medical students included audio-based resources (eg, podcasts),15,30,35 e-learning tools,13,24,32 and educational games 31,33. Finally, text-based resources (eg, e-books and research articles) were typically provided as supplemental (ie, additional reading) preparatory resources 12,13,17,26,34. In a case where multiple resources were provided for pre-class preparation, students reported accessing video-based resources more frequently than other tools 17.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, many programs use some mix of online and traditional lecture techniques, alternatively termed ''blended learning'' or ''hybrid learning,'' in a flipped classroom. 1,2 The term ''flipped classroom'' often may be applied to primary and secondary education, whereas the term ''inverted classroom'' is best applied to higher education. 3 The inverted classroom model (ICM) is a blended learning model that requires the student to acquire knowledge through self-directed learning online, and then attend face-to-face lecture (F2F) that compels the student to apply the knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…2,6,7 A flipped neuroanatomy course was described in a chiropractic college setting with no difference in performance or student satisfaction. 8 The authors concluded that ICM may not be the appropriate mode of delivery in courses that are concerned with intensive amounts of content.…”
Section: Introductionmentioning
confidence: 99%